2017
DOI: 10.1007/s00787-017-1032-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the dimensional structure and diagnostic algorithms between DSM-5 and ICD-11 PTSD in children and adolescents

Abstract: In contrast to the DSM-5, which expanded the posttraumatic stress disorder (PTSD) symptom profile to 20 symptoms, a workgroup of the upcoming ICD-11 suggested a reduced symptom profile with six symptoms for PTSD. Therefore, the objective of the study was to investigate the dimensional structure of DSM-5 and ICD-11 PTSD in a clinical sample of trauma-exposed children and adolescents and to compare the diagnostic rates of PTSD between diagnostic systems. The study sample consisted of 475 self-reports and 424 car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 29 publications
7
39
1
Order By: Relevance
“…() found that becoming physiologically reactive and upset in response to reminders of the trauma may represent key drivers in the symptom network. These divergent results may be partially explained by differing adult symptomatology, where reexperiencing symptoms may play a more central role (Sachser et al., ), and by the use of the DSM‐IV conceptualization of PTSD, which lacks our most central symptoms in the regularized partial correlation networks and the driving forces in the DAGs: negative trauma‐related cognitions and persistent negative emotional state .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…() found that becoming physiologically reactive and upset in response to reminders of the trauma may represent key drivers in the symptom network. These divergent results may be partially explained by differing adult symptomatology, where reexperiencing symptoms may play a more central role (Sachser et al., ), and by the use of the DSM‐IV conceptualization of PTSD, which lacks our most central symptoms in the regularized partial correlation networks and the driving forces in the DAGs: negative trauma‐related cognitions and persistent negative emotional state .…”
Section: Discussionmentioning
confidence: 99%
“…The mean total symptom score for the self‐report sample (CATS M US = 25.98 , CATS M Germany = 22.98, CATS M Norway = 20.68) and the caregiver‐report sample (CATS M US = 24.88 , CATS M Germany = 20.76, CATS M Norway = 15.84) reflects that traumatized children and adolescents in this study had a high mean severity of PTSS. Applying the DSM‐5 algorithm (itemscore ≥ 2) about 38% of children and adolescents could have been diagnosed with possible PTSD (Sachser et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of the ICD‐11 approach, Sachser et al. () found a PTSD diagnosis reduced to its core symptoms to be appropriate for children and adolescents. Furthermore, studies that investigated the PTSD factor structure in children and adolescents showed that treating the core PTSD symptoms as a specific entity distinct from depression and generic emotional distress provided the best model fit (Kassam‐Adams, Marsac, & Cirilli, ) and reduced PTSD‐depression comorbidity (Ford, Elhai, Ruggiero, & Frueh, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, Sachser et al. () argue that including intrusive memories might be important to account for developmentally different presentations of re‐experiencing symptoms in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%